Exploring Knowledge, Attitudes, and Practices of Medical Students towards Plagiarism: A Cross-Sectional Study - Iqra Aamir Dars, Syeda Hira Fatima, Muhammad Shahazeb, Abdul Moiz Shaikh, Fareesa, Allah Bachayo Rajar, Zameer Hussain Baladi, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: This study aims to determine how many medical students at MMC know about plagiarism, how they feel about it, and what they do about it. The study would find out how much they know about plagiarism, how they feel about it, how much they value academic integrity and originality, how smart they are, and what they think about academic honesty and intellectual property rights. Also, the study would look into what makes medical students feel good or bad about cheating. It could mean looking into educational interventions and policies that can raise knowledge of plagiarism and discourage it in the classroom. Methods: The Muhammad Medical College (MMC), located in Mirpurkhas, Sindh, Pakistan, conducted a cross-sectional study on MBBS students from the first to Final year. The self-administered, closed-ended questionnaire evaluated medical students' awareness, respect, and attitude toward plagiarism—a 3-option survey with closed questions. Two hundred medical students, ranging from (A) agree to (N) neutral to (DA) disagree. One hundred seventy medical students provided pros and disadvantages. Data were gathered, processed, and analyzed using Excel and SPSS 22. Results: First-question data demonstrates that most male and female students understand plagiarism's morality. Most students will understand citation and plagiarism if the second question is representative. Apathy helps students learn. The fourth question shows that most medical students—male and female—understand plagiarism's ethical implications. The subsequent questions show that medical students of different academic levels disagree on whether research newbies should be forgiven for plagiarism. Most students are agnostic or share this view. Based on these results, medical students doubt annual anti-plagiarism training. Some pupils need help to create an opinion. Most medical students, especially senior students, want tighter plagiarism laws. Practical Implication: Some learners need clarification on their stance or need extra knowledge and help before formulating an opinion. According to the research, most medical students, especially those in their last year, support discussing plagiarism at all academic levels. It shows a mature perspective of the students. Conclusion: This study illuminates medical students' views on plagiarism at undergraduate and graduate levels. Percentages show students' agreement, disagreement, and ambiguity. Data reveal that students of different academic years agree. These changes show that students question the efficacy of mandatory anti-plagiarism training at the start of each academic year Keywords: Plagiarism, Academic integrity, Intellectual property, Citation, Originality, Copyright infringement, Ethics, Attribution, Academic dishonesty, and Source acknowledgment.